Pengukuran Tekanan Cuff Endotracheal Tube Kontinyu dan Intermiten dalam Mencegah Kejadian Ventilator Associated Pneumonia di Ruang ICU : Systematic Review - Prima Khairunisa; Agung Waluyo; Denissa Faradita Aryani (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Background: Ventilator-Associated Pneumonia (VAP) is a major complication in mechanically ventilated patients, often resulting from microaspiration due to inadequate endotracheal cuff pressure. Maintaining optimal cuff pressure can be achieved through continuous or intermittent monitoring. Aim : To compare the effectiveness of continuous versus intermittent cuff pressure monitoring in preventing VAP. Methods: A systematic review was conducted across PubMed, Scopus, Taylor dan Francis, and ScienceDirect. Articles were screened based on publication year, title, abstract, and relevance. Results: Of 550 identified studies, 7 met the inclusion criteria. Four studies reported greater VAP prevention efficacy with continuous monitoring (p < 0.05, p = 0.06, p = 0.109, p = 0.02; OR 0.45, 95% CI = 0.22–0.89). Six studies found no significant impact on secondary outcomes, including ICU length of stay, ventilation duration, and mortality. Conclusion: Continuous cuff pressure monitoring ensures more stable pressure regulation, potentially reducing VAP risk. Further studies are needed to assess its impact on clinical outcomes